IMPLEMENTASI STRATEGI PEMBELAJARAN WRITING TO LEARN MENGGUNAKAN FORMAT TULISAN METAKOGNITIF UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF DAN KETERAMPILAN KOMUNIKASI SISWA SMA PADA MATERI USAHA DAN ENERGI - Alvin Syahrul Fauzan, - (2020)
The purpose of this study is to investigate the effectiveness of writing to learn strategies in improving students' cognitive abilities and communication skills as well as the relationships between the two variables in the Work and Energy topics. This study uses a quasi-experimental method with pretest-posttest control group design and is carried out in one of the high schools in Bandung, West Java. The instrument used to measure cognitive abilities was a 20-item multiple choice test while the instrument to measure communication skills was the task of writing in the form of a learning journal. The results of the analysis using normalized gain percentage indicate that the application of writing to learn strategies can improve cognitive abilities and communication skills with the medium category. The results of statistical tests also show that the writing to learn strategy is more effective in improving students' cognitive. The relationship between cognitive abilities and communication skills based on the results of the correlation test analysis classified as low criteria.